Boks : Z.Z.K. Polonia Warszawa-Z.K.S. Morski Gdynia. (Gdynia : [s.n.], 1949)
Zawody miały miejsce w kwietniu 1949 r. w Sali Urzędu Zatrudnienia na Grabówku.
Keywords: Boks -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Grabówek (Gdynia, Polska ; dzielnica) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne